PERCEPTIONS OF RISK FACTORS FOR ALZHEIMER'S DISEASE AMONG COMMUNITY LIVING, NON-DEMENTED OLDER AFRICAN AMERICANS. (16th November 2018) - Glover, C; James, B; CoCroft, S; Barnes, L
Abstract: Heightened Alzheimer's disease (AD) risk among African Americans represents a racial disparity in aging. An open question remains about variables that older African Americans perceive as AD risk factors. This study examines perceptions of potential AD risk factors among older non-demented African Americans. Participants from the Minority Aging Research Study (N=610; mean age=74.6 years, mean education=14.9 years, and 24% men) indicated how important 9 factors were in increasing one's risk of AD using a 4-point Likert scale from 1= not at all important to 4= extremely important. We examined perceptions of AD risk factors as a function of age, education, gender, and global cognition using separate logistic regression models for each factor. Of the 9 AD risk factors, genetics and God's Will were significantly related to predictors of interest. Younger participants (est. = -0.06, p= 0.02) and those with more education (est. = 0.14, p= 0.02) were more likely to report genetics as extremely important. Participants with more education were less likely to indicate God's Will as extremely important (est. = -0.14, p< .0005). Genetics and God's Will are perceived as salient risk factors for AD among subgroups of older African Americans. Younger and more educated African Americans perceive genetics as an important AD risk factor while those with less education perceive God's Will as an important AD risk factor. As older African Americans are not a monolithic group, findings can facilitate the design of effective and culturally competent educational tools for meaningful engagement with older African Americans about AD.